Macro uncertainty, unemployment risk, and consumption dynamics - Joonseok Oh; Anna Rogantini Picco (European Central Bank (ECB), 2024)
Households' income heterogeneity is important to explain consumption dynamics in response to aggregate macro uncertainty: an increase in uncertainty generates a consumption drop that is stronger for income poorer households. At the same time, labor markets are strongly responsive to macro uncertainty as the unemployment rate and the job separation rate rise, while the job finding rate falls. A heterogeneous agent New Keynesian model with search and matching frictions in the labor market can account for these empirical findings. The mechanism at play is a feedback loop between income poorer households who, being subject to higher unemployment risk, contract consumption more in response to heightened uncertainty, and firms that post fewer vacancies following a drop in demand.
Keywords: E12; E31; E32; J64; 330; Households' income heterogeneity; Precautionary savings; HANK and SaM